Leading school networks, hybrid leadership in action? - Townsend, Andrew (SAGE, 2015)
A range of different constructs are used to describe and define the way that leadership operates in education settings. This range can be presented as binary categories of leadership, in which either one, or the other form of leadership is preferred, but not both. An example of this is the contrast made between solo and distributed leadership. A more sophisticated alternative has been proposed, which is to consider leadership as a hybrid activity, one which entails a range of approaches inspired by varying ideals. Taking this ‘hybrid’ notion of leadership this article explores the nature of leadership in networks of schools. Illustrated with data from three case studies of school networks this article highlights some of the issues and tensions in the enactment of the hybrid forms of leadership encountered in these networks. This article concludes with some reflections on the adoption of hybrid notions of leadership in researching and enacting educational leadership and specifically on the place of school networks in that consideration.